Eileen Agar - angel of anarchy Angel of anarchy - Smith, Laura 1983-; Storey, Grace (Whitechapel Gallery, 2021)
Eileen Aigar (b.1899 Buenos Aires; d.1991 London) is an often overlooked but crucial figure within the development of European twentieth-century culture. Throughout her 80-year career she synthesised elements of both cubism and surrealism to create a unique personal style suffused with intelligence, wit, irreverence, and emotion through a century of huge social and political change. Previously appraised in relation to her connections to better-known male figures of British and European modernism such as Paul Nash, Ezra Pound, Roland Penrose and Paul Eluard, this first major survey of her work will place her firmly as a pioneering surrealist artist in her own right, illuminating her progressive attitudes to making, sexuality and art history. This timely monograph will feature rarely-seen work, as well as new contributions by writer Marina Warner, poet Daisy Lafarge and Aigar's biographer Andrew Lambirth.0This book is available in blue, red, mustard and maroon; books are shipped to customers at random. Exhibition: Whitechapel Art Gallery, London, UK (11.02.-13.05.2021)